Multiple Religious Belonging (MRB): Addressing the Tension between African Spiritualities and Christianity - Nweke, Kizito C. (Theology Today, 2020)
The question of religious pluralism has attracted many responses from the fields of interreligious dialogue and theology of religions. These responses, like inculturation, dialogue, and so on, have been concerned with "how" religions/spiritualities should be inclusive and imbue each other. However, the contemporary challenges of religious pluralism, ranging from the clamor for cultural identity to the structural and ontological differences among religions, suggest that the responses cannot create inclusivist interreligious contexts. One of these responses is the phenomenon of multiple religious belonging, which proposes that people could or should belong, believe, and practice as many religions as they want or can. In the Christianity–African spirituality context, this phenomenon poses some challenges for both Christianity and African indigenous spiritualities. This article intends to critically address the tensive constellation of African spiritualities and Christianity over the expectations of multiple religious belonging. It argues that there are discrepancies in the Christianity–African spiritualities constellation for multiple belonging. It suggests another approach to the question of religious/spirituality concatenation in Africa.
free
Keywords: African Indigenous spiritualities; CHRISTIAN spirituality; CHRISTIANITY & culture; Christianity; Igbo; Multiple Religious Belonging; RELIGIOUS diversity; inculturation; religious inclusivism-exclusivism